Aplikasi Chitosan Modified Carboxymethyl sebagai Coating Agent dalam Perbaikan Mutu Kertas - Hadiantoro, Sigit; Udjiana, S. Sigit; Azkiya, Noor Isnaini (Jurnal Teknik Kimia dan Lingkungan, 2020)
This study aimed to determine the effect of coating paper with Modified Carboxymethyl Chitosan (Cs-Mcm) to improve the quality of the paper, including paper grammage, tensile strength of paper, torn paper and a strong degree of fineness of the paper. The study was conducted by superimposing the Cs-Mcm as a coating agent on a paper-based pulp rice straw pulp waste paper and pulp mixture (rice straw and waste paper) with various concentration of acetic acid solvent 2%, 3%, 5% and 7%. The analysis showed the concentration of acetic acid solvent effect on the quality of recycled paper. Coating with Cs-Mcm in this study can improve the quality of recycled paper.